Suara anak bantaran sungai musi: studi photovoice pada kegiatan Sanitary Camp, Kampung Pandai 13 Ulu, Palembang - Najmah, Najmah; Ramawati, Mala; Azizah, Shinta; Zanjabila, Azmiya Rahma; Ar Rahma, Citra Ayu; Zhafirah, Yunida; Malfiro, Anisa; Ricko, M.; Rozin, Abid (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
The river is an important element in the life of the people who live around it. However, the high rate of river pollution makes the existence of the river cannot be used optimally. One of the causes of river pollution is the behavior of littering. The waste problem in Indonesia is still a thorny problem that has not been resolved until now. The increasingly polluted Musi River makes people vulnerable to the impacts of existing river pollution. Children are agents of change who need to be educated to produce quality young generations. Sanitary Camp is a program to educate about environmental health for young children so they will love their environment more. The method used is the Photovoice method which used photos as a means of expressing the views of participants. Participants in this community service were early childhood and elementary school children, totaling 35 people. There are 3 main stages of the photovoice process: making photographs, collective interpretation, and the process of dissemination of the resulting photos. The results of this community service activity reveal that the waste problem around the Musi River is caused by the habit of disposing of garbage that has been going on for generations in the community and the lack of waste management infrastructure as a practical solution for the community. There needs to be a role for the government to socialize and procure adequate waste management facilities and facilities for the sake of the sustainability of a healthy environment.